1983
DOI: 10.13182/fst83-a22854
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Catalyzed Conversion of Tritium Gas to Tritiated Water

Abstract: DE83 0123 50 P6CTCWS iF TOSS BEPOBT ABE IL1EGIBLE.It Ms to reproduces* fram the best available eapy to permit the broadest passible availability. INTRODUCTIONThe conversion of gaseous molecular tritium (T2) to the water form (DTO) is accompanied by a potential increase in hazard to people. If the tritium is located where people actually come in contact with it, the conversion from Tj to HTO represents a potential increase in hazard by a factor of 2S,000. That is, the health risk from an inhalation exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…The initial production rate was estimated as 2 X 10"8 mCi/mL-h. This value agrees well with previously reported values (2,6). In the absence of oxygen in gas phase, there was no measurable HTO formation, indicating that adsorbed water, which might be present on the inner surface of reaction vessel, did not participate in the formation of HTO in the present study.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The initial production rate was estimated as 2 X 10"8 mCi/mL-h. This value agrees well with previously reported values (2,6). In the absence of oxygen in gas phase, there was no measurable HTO formation, indicating that adsorbed water, which might be present on the inner surface of reaction vessel, did not participate in the formation of HTO in the present study.…”
Section: Resultssupporting
confidence: 94%
“…Many investigators have reported the formation of HTO via radiochemical (3), catalytic (4), and/or biochemical (5) processes. The effects of radiation such asand X-rays on HTO formation were also reported by Easterly (6) and Yang (7). An isotope-exchange reaction with water vapor in the atmosphere also takes part in the formation of HTO (7).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The kinetics of the conversion depend on the tritium concentration in air. The presence of a gamma radiation field may inhibit the conversion, and fields of 80% neutrons and 20% gamma have been observed to lead to a substantial limitation of the water formation rate in air [47].…”
Section: Tritium and Its Productionmentioning
confidence: 99%
“…Froa ths thermodynamics of the reaction 1/2 0 2 (5) one would assume that the trltlua Is completely oxidized. However, the gas phase homogeneous kinetics 32 and the gas phase heterogeneous kinetics are both slow. "…”
Section: E Oxidationmentioning
confidence: 99%